Perancangan Video Promosi Berbasis Motion Graphic di Madrasah Aliyah Wahid Hasyim - Rizal Arya Hafidz; Riyan Abdul Aziz; Hadis Turmudi (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
This research involves steps in creating promotional media that follows the ADDIE approach, with a focus on a case study conducted at MA Wahid Hasyim, Bangsri, Jepara. The video produced from this research aims to be the main promotional tool in the school environment, using a testing method using a Likert scale. Made in the form of motion graphic animation, the video was conceptualized creatively to provide an interesting introduction about the school, with the hope of attracting the interest of prospective students and other related parties in an innovative and interesting way.